2010
DOI: 10.5101/nml.v2i1.p42-48
|View full text |Cite
|
Sign up to set email alerts
|

Effect of hydrogen plasma treatment on the growth and microstructures of multiwalled carbon nanotubes

Abstract: The effect of hydrogen plasma treatment of iron oxide films on the growth and microstructure of carbon nanotubes (CNTs) by microwave plasma enhanced chemical vapor deposition process has been investigated. Microwave plasma was characterized in-situ using optical emission spectrometer. Morphology of the films was examined by scanning electron microscopy. Structural analysis was carried out by high resolution transmission electron microscopy (HRTEM) equipped with energy dispersive X-ray spectroscopy (EDS) and mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 24 publications
1
4
0
Order By: Relevance
“…In the present study, Ar/H 2 plasma pretreatment of the iron oxide film resulted into high density of nanoparticles (not shown here) which catalyzed the nucleation and growth of CNTs on the introduction of C 2 H 2 in the plasma [17]. The observation of a-C in samples A, and B and relative increase in the percentage of a-C with decreasing H 2 plasma pretreatment time of oxide films suggest the poor catalytic activity of oxide for CNTs growth as also reported by other methods [20,21]. In case of sample C, most of the iron oxide clusters are supposed to be reduced to Fe after 15 minutes of H 2 plasma treatment since plasma contains a lot of active H-species as observed by in-situ OES of the H 2 and H 2 +C 2 H 2 plasma in 200a900 nm wavelength range as shown in Fig.…”
Section: Resultssupporting
confidence: 70%
“…In the present study, Ar/H 2 plasma pretreatment of the iron oxide film resulted into high density of nanoparticles (not shown here) which catalyzed the nucleation and growth of CNTs on the introduction of C 2 H 2 in the plasma [17]. The observation of a-C in samples A, and B and relative increase in the percentage of a-C with decreasing H 2 plasma pretreatment time of oxide films suggest the poor catalytic activity of oxide for CNTs growth as also reported by other methods [20,21]. In case of sample C, most of the iron oxide clusters are supposed to be reduced to Fe after 15 minutes of H 2 plasma treatment since plasma contains a lot of active H-species as observed by in-situ OES of the H 2 and H 2 +C 2 H 2 plasma in 200a900 nm wavelength range as shown in Fig.…”
Section: Resultssupporting
confidence: 70%
“…Hydrogen plasma treatment is also used for CNT synthesis, e.g., for the regeneration of the catalyst deposited on the substrate [ 32 ]. It was shown that full-cycle CNT growth in hydrogen plasma is possible in the presence of carbon [ 33 , 34 ].…”
Section: Introductionmentioning
confidence: 99%
“…They found that for too high oxygen plasma power, chemical etching occurs at the surface of the CNT, thus destroying its structure. Srivastava et al (2010) studied the effect of hydrogen plasma treatment on oxide films on the growth and microstructures of MWCNTs and reported that the oxide films without the H 2 plasma pretreatment or treated for lesser time resulted in CNT films with high percentage of carbonaceous particles and with embedded particles/nanorods distributed discontinuously in the cavity of the nanotubes. They reported that the size and morphology of Co-catalytic seeds varied with hydrogen plasma treatment time.…”
Section: Introductionmentioning
confidence: 99%
“…The effect of plasma treatment, plasma parameters and plasma powers on the growth, structure (Lee et al 2002;Felten et al 2005;Zhu et al 2005;Wen et al 2006;Abdi et al 2008;Srivastava et al 2010;Lee et al 2012;Yau and Tsai 2012) and field emission properties (Haaland et al 1996;Bonard et al 1998;Zhi et al 2002;Ahn et al 2003;Srivastava et al 2005Srivastava et al , 2010Xu et al 2006;Feng et al 2007;Lee et al 2009;Sodha et al 2010 Sharma andTewari 2011a) of a carbon nanotube (CNT) has been an active field of research for many years. Yau and Tsai (2012) studied the effect of the localized lateral growth of multiwalled carbon nanotubes (MWCNTs) with ammonia plasma post-treatment and their experimental results showed that upon exposure to ammonia plasma, electrical properties of CNTs are found to increase.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation